Managing Capabilities for Supply Chain Resilience Through it Integration - Gružauskas, Valentas; Vilkas, Mantas (Economics and Business, 2017)
The trend for e-commerce, estimated population size to 11 billion by 2050, and an increase in urbanization level to 70 % is requiring to re-think the current supply chain. These trends changed the distribution process: delivery distances are decreasing, the product variety is increasing, and more products are being sold in smaller quantities. Therefore, the concept of supply chain resilience has gained more recognition in recent years. The scientific literature analysis conducted by the authors indicate several capabilities that influence supply chain resilience. Collaboration, flexibility, redundancy and integration are the most influential capabilities to supply chain resilience. However, the authors identify that the combination of these capabilities to supply chain resilience is under researched. The authors indicate that by combining these capabilities with the upcoming technologies of industry 4.0, supply chain resilience can be achieved. In the future, the authors are planning to conduct further research to identify the influence of these capabilities to supply chain resilience, to quantify supply chain resilience, and to provide further practices of industry 4.0 concept usage for supply chain resilience.